The effect of abdominal fat parameters on percutaneous nephrolithotomy success - İLBEY, YUSUF ÖZLEM; Cakmak, Ozgur; Tarhan, Huseyin; Cimen, Sertac; Ekin, Rahmi Gokhan; Akarken, Ilker; Oztekin, Ozgur; Can, Ertan; Suelozgen, Tufan; Ilbey, YUSUF ÖZLEM (My University, 2016)
Introduction: Obesity has been suggested to lower the success of percutaneous nephrolithotomy (PCNL). However, the relationship between abdominal fat parameters, such as visceral and subcutaneous abdominal adipose tissue, and PCNL success remained unclear. In this study, we aimed to investigate the effect of abdominal fat parameters on PCNL success.